THE ANTECENDENT OF CUSTOMER SATISFACTION THROUGH ELECTRONIC SERVICE QUALITY IN ONLINE URBAN CONSUMER SHOPPING IN DKI JAKARTA - Wardhana , Ali; Kembau, Agung Stefanus; Kumaat , Arief Perdana; Sunara, Tristano Aviel (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2023)
This study aims to analyze the effect of electronic service quality variables on consumer satisfaction in the context of online shopping and the antecedents of electronic service quality. This study involved 119 respondents who actively shopped online. Data were collected through questionnaires and analyzed using the Partial Least Square (PLS) method. The results showed that the electronic service quality variable has a significant influence on consumer satisfaction in online shopping. In addition, there are 2 variables that have a significant influence on the quality of electronic services, namely security and compliance. However, interestingly, the results of the analysis also state that the consumer service variable has no influence on the electronic service quality variable. The results of this study indicate the importance of business actors in marketplaces or other online shopping places to ensure high service quality to increase consumer satisfaction. In addition, security and compliance must also be a major concern to improve the quality of e-services. This research provides valuable insights for marketplace industry players and other online shopping places in formulating more effective marketing strategies using security and fulfillment variables to increase customer satisfaction. Keywords: Consumer service, Security, Fulfillment, Electronic service quality, Consumer satisfaction